Is the relative age effect just a European problem? A comprehensive analysis of birth date distribution and its impact on player selection at the 2023 FIFA Women`s World Cup - Pérez-González, B.; León-Quismondo, J.; Bonal, J.; Iván-Baragaño, I.; Fernández-Luna, Á.; Burillo, P. (PLOS ONE, 2025)
This study examines the presence and implications of the Relative Age Effect (RAE) in the 2023 FIFA Women`s World Cup, focusing on the distribution of players` birth dates across continents and professional levels. Utilizing a sample of 735 players, a Poisson regression was conducted on the weekly birth frequency to determine the significance of the fit to a Poisson regression curve. Despite the lack of a significant RAE across the overall player population, our findings reveal notable geographical and positional variations. Specifically, European players, particularly goalkeepers and defenders, alongside the top 4 classified teams and nations with a substantial number of federation licenses, exhibit a significant RAE, suggesting a substantial impact on player selection favouring those born earlier in the year. Conversely, players from Africa, America, Asia, and Oceania do not show a significant RAE, indicating variability in its manifestation across different football environments.